Impact of V179D/E mutations on antiretroviral therapy outcomes in people living with HIV-1: a 3-year retrospective study - Lv, Shiyun; Lan, Yun; Li, Quanmin; Ling, Xuemei; Li, Junbin; Wen, Chunyan; Li, Yonghong; Chen, Jingliang; Chen, Xiejie; Cai, Weiping; Tang, Xiaoping; Li, Linghua (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHIV-1 mutation V179D/E can confer potential low-level resistance to multiple non-nucleoside reverse transcriptase inhibitors (NNRTIs), and its detection rate has increased in recent years. However, its effect on antiretroviral therapy (ART) outcomes remains unclear.MethodsThis study included people living with HIV-1 (PLWH) with only V179D/E mutation detected by pre-treatment drug resistance (PDR) testing at Guangzhou Eight People’s Hospital between January 2018 and December 2022. Two control groups were matched 1:1:1 using propensity score matching (PSM): a PDR-negative group and an NNRTI-DR group with low-level or higher NNRTI resistance. Virological and immunological outcomes were compared over 3 years. Logistic regression analyzed virological failure (VF) risk factors in the V179D/E group and assessed acquired drug resistance (ADR).ResultsAmong 6021 patients tested, the detection rate of V179D/E was 14.8%. After exclusions, 626 patients were included in this study. Additionally, 195 patients met the criteria for the NNRTI-DR group. After 1:1:1 PSM, the baseline characteristics were balanced across the three groups. In 1 year, the V179D/E group showed lower virological suppression and higher VF than the PDR-negative group, with no significant difference from the NNRTI-DR group. Differences disappeared by years 2 and 3. In the V179D/E group, NNRTI-based regimens increased VF risk, while baseline CD4+ T cell counts >200 cells/μL were protective. Among 37 patients with VF tested for ADR in the V179D/E group, 54.1% developed new mutations, 85.0% of whom were on efavirenz (EFV)-based regimens.ConclusionsV179D/E is highly prevalent among ART-naïve PLWH in Guangzhou and may impair early virological response to NNRTI-based regimens, particularly EFV-based regimens while increasing ADR risk.